PSYCHOLOGICAL APPROACH TO THE CHARACTERS OF E-LITERATURE FINAL FANTASY TACTICS: THE WAR OF THE LIONS - Jauza Munirah and Amrin Saragih (LINGUISTICA, 2018)
The aim of this study is to investigate the structures of personalities, the driving forces behind behaviors, the interweaving roles of the characters in a videogame titled Final Fantasy Tactics: The War of the Lions and how those roles affect the overall literary works. The type of this research is qualitative. The .iso, script as well as the documentation videos of Final Fantasy Tactics: The War of the Lions are the sources of the data. The data are the utterances and actions which conveys the characters’ perceptions in a particular physical and social environments, their needs, wishes, intentions, memories of past events and their imagining about future, their ways to overcome inferiority, the future they envision, their goals and expectations. The writer finds that the seemingly opposite characters actually share similar goals: to fight the imbalances, particularly the social disparity between noble and commoner and to make the world a better place. Both characters start to differ because of their differences in backgrounds which lead one to seek power while the other one abandoned power. Each characters have their own assigned roles based on the application of Jung’s archetypes, and they share similar roles. But, while most a character’s roles changes to the shadow sides (the negative sides) because of the situations that occured, the other character retains the positive qualities of the archetypes. Both characters become the antithesis of each others and their interweaving roles lead to a deeper and complex interpersonal conflicts, a more interesting story, as well as a great emotional impacts.